2017
DOI: 10.1177/1932296817695337
|View full text |Cite
|
Sign up to set email alerts
|

NICH at Its Best for Diabetes at Its Worst: Texting Teens and Their Caregivers for Better Outcomes

Abstract: Background: There is growing evidence for the feasibility of text-based interventions for pediatric patients with type 1 diabetes (T1D). However, less is known regarding whether the use of personalized text messages with high-risk youth and their caregivers is associated with improvements in youth health. This study examines the use of diabetes-specific texts and associated health outcomes for participants of the Novel Interventions in Children's Healthcare (NICH) program. Methods:Text messages sent to youth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…More intensive coordination of care with patients and increased family engagement are some of the additional strategies for the prevention of recurrent episodes of DKA. The Novel Interventions in Children's Healthcare programme uses care coordination with the family and telemedicine as a part of the preventive strategy to engage young people with multiple hospitalizations for DKA 224 . This work used text messages and other forms of communication with the adolescents and showed that daily communication decreased DKA readmissions.…”
Section: Clinical Prioritiesmentioning
confidence: 99%
“…More intensive coordination of care with patients and increased family engagement are some of the additional strategies for the prevention of recurrent episodes of DKA. The Novel Interventions in Children's Healthcare programme uses care coordination with the family and telemedicine as a part of the preventive strategy to engage young people with multiple hospitalizations for DKA 224 . This work used text messages and other forms of communication with the adolescents and showed that daily communication decreased DKA readmissions.…”
Section: Clinical Prioritiesmentioning
confidence: 99%
“…One meta-analysis of mobile phone interventions showed a 3.3-mmol/mol (0.3%) reduction in HbA 1c in those with Type 1 diabetes receiving the mobile intervention [9]. E-mail: lori.laffel@joslin.harvard.edu component, demonstrated a reduction in diabetic ketoacidosis-related emergency department visits [11]. E-mail: lori.laffel@joslin.harvard.edu component, demonstrated a reduction in diabetic ketoacidosis-related emergency department visits [11].…”
Section: Introductionmentioning
confidence: 99%
“…One meta-analysis of mobile phone interventions showed a 3.3-mmol/mol (0.3%) reduction in HbA 1c in those with Type 1 diabetes receiving the mobile intervention [9]. An intensive intervention, the Novel Interventions in Children's Healthcare (NICH) programme, which targeted high-risk young people with Type 1 diabetes and included a text-messaging component, demonstrated a reduction in diabetic ketoacidosis-related emergency department visits [11]. There may also be additional, non-glycaemic, benefits of text-messaging interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the clinical and economical information from our intervention can be applied to other aspects of health care, such as diabetes care [ 37 , 38 ], eldercare [ 39 ], and many other chronic diseases where patient treatment fatigue is a known barrier [ 15 , 40 - 43 ]. As bidirectional mHealth offers patients real-time advice from HCPs and improves self-management of chronic diseases, the benefits may extend beyond what we are able to quantify.…”
Section: Discussionmentioning
confidence: 99%